KAJIAN PENYAKIT YANG DISEBABKAN OLEH CENDAWAN PADA TANAMAN CABAI MERAH (Capsicum annum L.) DI PERTANAMAN RAKYAT KABUPATEN BREBES - Nita Wahyu Suwardani; Purnomowati Purnomowati; Eddy Tri Sucianto (Scripta Biologica, 2014)
This research aimed to determine the various diseases caused by fungi, to identify the fungi causing the disease, and to determine the most dominant disease in red chili crops (Capsicum annum L.) from smallholder agriculture located in Kaligiri Sirampog Brebes. The research was a survey applying purposive random sampling technique. This study collected samples from five locations, within five plots placed diagonally at each site. This study picked ten infected plants from each plot, identified the disease; isolated and identified the fungi causing the disease. This research also measured the environmental factors such as temperature, humidity, and soil pH. The results showed diseases in red chili plants (Capsicum annum L.) were the leaf spot caused by Cercospora sp., the anthracnose caused by Colletotrichum sp., and the fusarium wilt caused by Fusarium sp., and the most dominant were leaf spot disease.